(untitled) (Bangladesh Journal of Infectious Diseases, 2021)
A 5 years old child with pertussis reported to us with a unique complication not mentioned in the literature. He was thoroughly examined and investigated to find out cause for his lower motor neuron (LMN) facial palsy but purtussis seemed to be the sole reason. With treatment of purtussis the patient showed marked improvement of neurological deficit. Bangladesh Journal of Infectious Diseases 2020;7(2):107-109